STRATEGI GURU PAI DALAM MENINGKATKAN MINAT BELAJAR PESERTA DIDIK (Studikasus Di Kelas XI SMK Queen Al Falah Mojo Kediri) - shohibulfaza (LPPM STAI DARUSSALAM LAMPUNG, 2022)
ABSTRACT This research is motivated by the number of lessons that are carried out by a teacher that is less than optimal, so that it has an impact on the learning interest of students in following the ongoing learning process. The focus of this research is: (1) What is the strategy of PAI teachers in increasing student interest in learning in class XI SMK Queen Al-Falah?. (2) What is the impact of the PAI teacher's strategy on students' interest in learning?. This research is a qualitative descriptive research. The results of this study are the strategies adopted by PAI teachers at Queen's Vocational School in increasing interest in learning from the perspective of Hamzah B. Uno, namely: an organizational strategy, which includes the use of LKS books, textbooks and the internet. Delivery strategy, which includes the use of inquiry learning strategies and lecture, discussion, and question and answer methods. Learning management strategies that include the use of lesson plans and motivation for the importance of learning PAI. As for the impact of implementing this strategy, student interest can experience changes, namely: student readiness in receiving and preparing material to be discussed, student attendance in participating in learning, student activity in participating in discussions, final grades of learning outcomes also increased. Keywords: teacher strategy, interest in learning ABSTRAK Penelitian ini dilatarbelakangi oleh beberapa pembelajaran yang di lakukan oleh seorang guru kurang maksimal, sehingga berdampak pada ketertarikan belajar siswa ketika aktivitas belajar mengajar dilakukan. Fokus pada penelitian ini adalah: (1) Bagaimana strategi guru PAI dalam meningkatkan minat belajar peserta didik di kelas XI SMK Queen Al-Falah?. (2) Bagaimana dampak strategi guru PAI terhadap minat belajar peserta didik?. Penelitian ini memakai penelitian deskriptif kualitatif. Hasil dari penelitian mendapat hasil strategi yang di laksanakan oleh guru PAI di SMK Queen dalam memacu ketertarikan belajar persepektif Hamzah B. Uno yaitu: strategi pengorganisasian, yang mencakup penggunaan buku LKS, buku paket serta internet. Strategi penyampaian, yang mencakup penggunaan strategi pembelajaran inkuiri dan teknik ceramah, diskusi, serrta tanya jawab. Strategi pengelolaan pembelajaran yang mencakup penggunaan RPP serta motivasi terhadap pentingnya belajar PAI. Adapun dampak dari penerapan strategi tersebut minat siswa dapat mengalami perubahan yaitu: kesiapan siswa dalam menerima maupun mempersiapkan materi yang akan di bahas, kehadiran peserta didik dalam mengikuti pembelajaran, keaktifan siswa dalam mengukuti diskusi, dan nilai akhir dari hasil pembelajaran semuanya mengalami peningkatan. Kata kunci: Strategi guru, minat belajar